Knowledge Attitude Practice Study Regarding Age Related Macular Degeneration among Diagnosed Patients at A Tertiary Eye Hospital in Central Nepal - Subedi, Kumudini; Upadhyay, Hari Prasad; Shrestha, Anju (Journal of National Heart and Lung Society Nepal, 2025)
Background: Age Related Macular degeneration (ARMD) is among the five leading causes of blindness worldwide and among the top causes of retinal blindness. Patients should be made aware of the implications of the disease.Methods: A novel Knowledge Attitude Practice (KAP) questionnaire with 25 questions was formulated in understandable language. 50 patients diagnosed with any stage ARMD were administered the questionnaire verbally with the aid of skilled ophthalmic personnel and the answers recorded on questionnaire sheets. Results: Socio-demographic parameters of patients enrolled in the study included male: female ratio of 24:26, a majority from Chitwan district (88%). Most patients were illiterate (62%) and farmer by profession. 60% had no prior awareness of the disease. 76% had good knowledge of disease and 56% had a positive attitude towards the disease and 70% had good practice regarding the disease. However, there was no significant association between the level of knowledge attitude or practice with gender, area of residence, occupation or educational status.Conclusion: There is a gap in awareness regarding ARMD in the elderly population, even in patients suffering from the disease. Mass awareness programs are necessary targeting the community level and the country at large.